Deriving erosion thresholds of freshly deposited cohesive sediments from the port of Hamburg using a closed microcosm system - Witt, M.; Patzke, J.; Nehlsen, E.; Fröhle, P. (Frontiers in Marine Science, 2024)
The quantification of the erodibility of cohesive sediments is fundamental for an advanced understanding of estuarine sediment transport processes. In this study, the surface erosion threshold τc for cohesive sediments collected from two sites in the area of the Port of Hamburg in the River Elbe is investigated in laboratory experiments. An improved closed microcosm system (C-GEMS) is used for the erosion experiments, which allows the accumulation of suspended sediment concentration (SSC) over an experimental run. A total of 34 erosion experiments has been conducted with homogenized samples and bulk densities between 1050 kg/m³ and 1250 kg/m³. The covered range of bulk densities is seen to represent the values commonly exhibited by freshly deposited cohesive sediments. Two approaches to derive τc based on the erosion rate (ε-method) and the SSC (SSC-method) were elaborated and compared. For both approaches, only one parameter has to be set in order to facilitate transferability to other devices. The results show a better performance of the SSC-method in terms of lower uncertainties, especially at the upper application limits of the utilized C-GEMS. The application of the SSC method yields values for τc between 0.037 N/m² and 0.305 N/m², continuously increasing with bulk density. Repetition tests proved the repeatability of the experimental procedure and utilized methods to derive τc. The derived data for τc is used to fit two mathematical models: i) a highly empirical model relating τc to dry bulk density and ii) a recently proposed model relating τc to the physical properties of the sediment-mixture. While the derived parameters for the first model vary widely for the two sampling sites, the fit-parameter for the latter model is virtually independent of the investigated site, suggesting the superiority of this approach.